Specific interaction of pancreatic elastase and leucocytes to produce oxygen radicals and its implication in pancreatitis. Issue 11 (November 1994) - Tsuji, N; Watanabe, N; Okamoto, T; Niitsu, Y
Abstract : Many previous reports using experimental animal models of pancreatitis have suggested that oxygen free radicals play an important part in initiation and development of pancreatitis. Infiltration of inflammatory cells–that is, neutrophils, lymphocytes, and monocytes–has been seen in damaged pancreatic glands of animal models and patients with pancreatitis. As neutrophils are known to be the highest producer of oxygen free radicals among these inflammatory cells, it seems plausible that oxygen free radicals produced by neutrophils have some pathoaetiological meaning in pancreatitis. This study measured the superoxide production by neutrophils obtained from patients with acute and chronic pancreatitis and then examined the effects of pancreatic enzymes on superoxide production. Patients showed significantly higher superoxide production by 4 beta-phorbol 12 beta-myristate 13 alpha-acetate (PMA) stimulated neutrophils than healthy controls. Among the three pancreatic enzymes, amylase, trypsin, and elastase, elastase was the only one that increased the superoxide production by PMA stimulated neutrophils, by an increment of 1.5-fold. It also increased the activity of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase prepared from PMA stimulated neutrophils by a factor of 2.1. High affinity and low affinity binding sites for elastase on neutrophils were identified. These results suggest that elastase plays a part in the development of pancreatitis by enhancing superoxide production of neutrophils.